Transgenerational transmission of eating habits - Mauro Fisberg; Nathalia Gioia; Priscila Maximino (Elsevier, 2024)
Objective: To investigate the relationship between the biopsychosocial environment and eating habits and behaviors that lead to the selection and consumption of certain food from the earliest stages of life. To clarify whether there is an interaction between genetic and epigenetic factors, and how they shape eating habits. Data source: A narrative review based on research in PubMed and Web of Science electronic databases was carried out over the last 10 years, searching the title and summary fields using the keywords Children OR adolescents Feeding Behavior eating OR Dietary Habits OR Eating Behavior OR Eating Habits OR Children obesity. Data synthesis: The generational transmission of eating habits is related to the home, community, and school environments, mainly during the first years of life, and can exert the modulation of habits during all stages of life. During childhood, the family's role in consolidating eating habits is very broad and ranges from choosing foods to prioritizing family meals, including the lifestyle. Conclusions: Eating habits are transmitted from parents to children in different ways: environmental, emotional, social, and educational. In cases of obesity, a greater association of genetic influence can be observed.